The Value of Non-Binding Announcements in Public Goods Experiments: some Theory and Experimental Evidence - Gunther Markwardt; Marcus Dittrich; Michael Berlemann (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2004)
In this paper we present three simple theoretical models to explain the influence of the possibility to make non-binding announcements on future investment behaviour in public good settings. Our models build on the idea that voluntary contributions to the supply of a public good might be motivated by some form of joy of giving. We show that the possibility to make non-binding announcements has a positive effect on cooperative behaviour, especially if individual announcements and factual investments are communicated to the players after each round. We also show that this result holds true even though the players have an incentive to overstate their true degrees of cooperativeness. Altogether, our theoretical considerations point in the direction that revealing as much information on individual intentions and factual behaviour as possible enhances cooperative behaviour. These conclusions are broadly confirmed by the results of a series of classroom experiments we present.
Keywords: C92; D74; H41; 330; Public goods; Announcements; Joy of giving; Experimental economics; Öffentliches Gut; Experiment; Ankündigungseffekt; Altruismus; Nichtkooperatives Spiel; Theorie